Immunization Status and Risk of Measles/Rubella Incidence During Outbreak - Yurnila, Yurnila; Martha, Evi (Jurnal Kesehatan - STIKes Prima Nusantara, 2024)
Background: In 2018, measles remained a leading cause of morbidity and mortality worldwide, with over 9.7 million cases and more than 140,000 deaths associated with this disease. Additionally, rubella also has long-term health consequences, with an estimated 103,000 infants born with Congenital Rubella Syndrome (CRS). In 2022, there was a significant increase in the number of laboratory-confirmed measles cases, totaling 4,845 cases, with six resulting in death (CFR 0.1%). Some of the provinces most affected were Aceh, West Sumatra, and East Java. In 2022, the city of Pariaman was declared a state of emergency (KLB) for measles.Aims: To analyze the link between immunization status and measles/rubella incidents during the KLB event in Pariaman City in 2022.Method: Quantitative research with a case-control design. In this study, the researchers used secondary data contained in the annual report of Pariaman City Health Service for 2022. The researchers employed a parametric test with Chi-Square statistical test using the IBM SPSS computer program to determine the interaction between the two variables.Results: The results of the study showed that there was a relationship between a history of immunization and the occurrence of measles/rubella in Pariaman City. P = 0.032 (p < 0.05). An OR value of 3.25 (95% CI = 1.209 – 8.733) indicated that a history of non-immunization had a 3.25 times greater risk of exposure to measles/rubella than a history of immunization.Conclusion: Immunization history affects the outbreak in Pariaman City in 2022.